Evaluasi Mutu Fisikokimia dan Aktivitas Antioksidan Minuman Isotonik Ekstrak Batang Tali Kuning (Anamirta cocculus (L.) Wight & Arn.) - Nadziatul Khasanah; A.M. Muslihin; Marzella Dea Rossardy; Justitia Cahyani Fadli (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
as having potential as a natural antioxidant agent. One potential way to utilize this plant is by innovating it into an isotonic drink product. Objective: This study aimed to evaluate the physicochemical properties and antioxidant activity of an isotonic drink formulated with yellow rope stem extract. Methods: he extraction process was conducted using the maceration method with 70% ethanol as the solvent. The isotonic drink was developed into three formulas, which were then tested for their physicochemical properties and antioxidant activity using the DPPH method. Results: The results indicated that the best formula was FII, with an overall hedonic score of 4,6 (neutral). All three formulas showed identical pH values (4,0) and Total Soluble Solids (TSS) of 7%, while the total acidity decreased progressively: FI (1,024%), FII (0,896%), and FIII (0,704%). The isotonic drinks from yellow rope stem extract for formulas FI, FII, and FIII produced IC50 values of 35,61, 46,56, and 57,69 μg/mL, respectively. Based on these data, FI and FII were identified as having very strong antioxidant intensity, while the FIII showed activity classified in the strong category. Conclusion:.The test results demonstrate that the isotonic drink made from yellow rope stem extract exhibits antioxidant potential with intensity levels ranging from strong to very strong.